2001
DOI: 10.1152/advances.2001.25.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics for Medical Students

Abstract: The flow of blood through the cardiovascular system depends on basic principles of liquid flow in tubes elucidated by Bernoulli and Poiseuille. The elementary equations are described involving pressures related to velocity, acceleration/deceleration, gravity, and viscous resistance to flow (Bernoulli-Poiseuille equation). The roles of vascular diameter and number of branches are emphasized. In the closed vascular system, the importance of gravity is deemphasized, and the occurrence of turbulence in large vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 3 publications
2
36
0
2
Order By: Relevance
“…However, a difference of 3 to 4 m in retinal vessel diameter corresponds to a difference in resistance of 13% to 17% according to the Poiseuille equation whereby resistance varies by the inverse of the fourth power of the diameter. 40 This change in resistance corresponds to an increase in pressure of 13% to 17%. We have also previously shown that changes of this magnitude predict the incidence of hypertension 18 and coronary heart disease, 23 and other researchers have found even smaller decreases in retinal arteriolar caliber are associated with significant increase in systolic blood pressure (eg, a 1.1-m reduction in arteriolar caliber is associated with a 10-mm Hg increase in systolic blood pressure).…”
Section: Discussionmentioning
confidence: 99%
“…However, a difference of 3 to 4 m in retinal vessel diameter corresponds to a difference in resistance of 13% to 17% according to the Poiseuille equation whereby resistance varies by the inverse of the fourth power of the diameter. 40 This change in resistance corresponds to an increase in pressure of 13% to 17%. We have also previously shown that changes of this magnitude predict the incidence of hypertension 18 and coronary heart disease, 23 and other researchers have found even smaller decreases in retinal arteriolar caliber are associated with significant increase in systolic blood pressure (eg, a 1.1-m reduction in arteriolar caliber is associated with a 10-mm Hg increase in systolic blood pressure).…”
Section: Discussionmentioning
confidence: 99%
“…Although cardiac output and sympathetic activity may be elevated in the early stages of hypertension, increased peripheral resistance is the main driver for chronically elevated BP (Heagerty et al, 2010). Resistance to flow can be influenced by blood viscosity, vessel length and vessel diameter, with resistance being inversely proportional to the fourth power of the vessel's radius (Poiseuille's law) (Badeer, 2001;Sriram et al, 2014). Small arteries which provide the greatest percentage contribution to peripheral resistance have been termed resistance arteries, and are defined as pre-capillary vessels composed of a relatively thick media layer and having internal diameter of approximately 100-300 μm (Mulvany & Aalkjaer, 1990;Korsgaard et al, 1993;Christensen & Mulvany, 2001;Heagerty et al, 2010).…”
Section: Resistance Arteries and Essential Hypertensionmentioning
confidence: 99%
“…This formula has been used to determine the resistance of capillary beds. According to this formula, the total resistance is less than that of any individual resistance, and if the number of vessels in parallel increases, the total resistance should decrease [8]. However, with the increase in the vessels in parallel, the total cross-sectional area should be greater than that of the inlet and outlet.…”
Section: Parallel Network Resistancementioning
confidence: 99%